STRATEGIC PARADIGMS IN INDONESIAN HIGHER EDUCATION:NAVIGATING COMPLEXITIES, EMBRACING GLOBAL DYNAMICS, AND PROPELLING QUALITY ENHANCEMENT - Abdul Rozak; Usman Tahir, Abdul Muid Fabanyo, Misdi, Tanwir (International Journal of Teaching and Learning, 2024)
This research investigates the strategic paradigms shaping Indonesian higher education, exploring how institutions navigate complexities, respond to global dynamics, and propel quality enhancement. Employing a thorough literature review methodology, the study synthesizes existing knowledge, identifies gaps, and contributes to the scholarly discourse. Focal points include the evolution of curriculum structures, the impact of global dynamics, and initiatives fostering quality enhancement. The findings illuminate strategic shifts in response to the Fourth Industrial Revolution, globalization, and the imperative for quality improvements. The research underscores the interconnectedness of these paradigms and their implications for the future of higher education in Indonesia. By examining the intricate interplay between local needs and global trends, this study provides insights into institutions' adaptive strategies, laying a foundation for future advancements and addressing the challenges posed by a rapidly changing educational landscape.